Caracterización hidrogeológica de la localidad de sayá - Álvarez R., Fernando H. (2010)
The town of Saya is in the eastern sector of the Santa Elena Peninsula (Ecuador). Semi arid climate fostered by the geographical location along with the increased demand for water must have knowledge of groundwater resources. Thus the main objective of this thesis is to characterize the local aquifer system considering the hydrogeological performance. Information has been gathered from several previous works are well developed and field tasks and office in 2008-2009. The results show that the local system is composed of two hydrogeological units. Formation sands and sandstone Tablazo possibly Sugar Group with an average 134.4 m2/day. The hydraulic flow in the region basically runs from northwest to southeast and locally undergoes a change of address to the deposits, which are exposed to a higher operating system. The electrical conductivities ranging from 500 - 4000 μS / cm, we ca